Community social capital, migration status, and Chinese rural children's psychosocial development. Issue 2 (12th December 2021) - Tian, Felicia F.; Jing, Yongchao; Liu, Jingming
Abstract: Migration's impact on Chinese rural children's psychosocial development is the subject of growing research attention. While scholars highlight the critical role of social support, they have yet to systematically examine whether and how community social capital, which provides proximal social support for families, affects rural children's psychosocial development as well as whether such associations vary by children's migration status. Using data from the child component of the 2012 Chinese Urbanization and Labor Migration Survey, this article shows that community social capital reduces children's behavioral and emotional problems; however, left‐behind children and migrant children gain less from community social capital than children with at‐home parents. In addition, left‐behind girls fare worse and gain less from community social capital than left‐behind boys. Together, these findings imply that community social capital reinforces the disadvantaged psychosocial development of rural children who experience parental migration and evidence the enduring gender inequality in rural China.